Genome-wide identification of WOX family members in nine Rosaceae species and a functional analysis of MdWOX13-1 in drought resistance - Lv, Jiahong (Plant science : an international journal of experimental plant biology, 2023)
Copyright © 2022 Elsevier B.V. All rights reserved.